Adaption and validation of simplified Chinese version of the Low Back Pain Knowledge questionnaire (sC-LKQ) - Wang, Zhe; Xie, Yinyao; Dózsa-Juhász, Olívia; Makai, Alexandra; Járomi, Melinda (Frontiers in Public Health, 2023)
Introduction: Low back pain (LBP) knowledge questionnaire (LKQ) was developed by a Brazilian research group in 2009. It has been cross-culturally adapted to many languages with good reliability and validity. This work aimed to translate and validate the LKQ into a simplified Chinese version and to evaluate the self-efficacy in LBP among Chinese participants from China and Hungary. Methods: A total of 431 people participated in this research, which lasted from September 2021 to June 2022 and was conducted on the Credamo online platform.The simplified Chinese LKQ (sC-LKQ) was generated through translation and crosscultural adaptation guidelines. The participants were selected to fill out demographic questions, the sC-LKQ, and the Roland-Morris Disability Questionnaire (RMDQ).The reliability and validity of the data were evaluated using SPSS 28.0.The sC-LKQ showed good internal consistency (Cronbach's alpha was 0.79), and the intraclass correlation value was 0.85. There were five components in the questionnaire with good construct validity. The scores of RMDQ had negatively correlated with sC-LKQ.In the Chinese population, the sC-LKQ demonstrated excellent psychometric qualities and could be used to evaluate self-efficacy in clinical practice and research.